MODAL WORDS OF POSSIBILITY IN THE TRANSLATION FROM RUSSIAN INTO CHINESE: HULL-ORIENTED ANALYSIS - Nurullina, Guzel M.; Yuan, Tao; Usmanova, Liliya A. (Gênero & Direito, 2019)
The article deals with the modal words with the meaning of the possibility in the translation aspect from Russian to Chinese. The attention is focused on the ways of possibility modality expression in the linguistic corps of the languages being studied. The relevance of this work is determined by the fact that it relies on a contrastive description of the linguistic facts of Russian and Chinese languages and is carried out in line with the modern comparative-typological approach to the study of modal words with the meaning of possibility. The article attempts to study the modal words with the meaning of possibility in the framework of Russian-Chinese translation. In order to determine the features of possibility modality translation, the following studies were carried out: 1) the modal words with the possibility value were divided into four types; 2) the search was performed for the correspondence of words and word combinations in a parallel corpus. The scientific work also presented an experimental study, which allows us to conclude that each type of modal words shows different conformity trends in translation: zero correspondence, correspondence and compensation. The quantitative analysis shows that the Russian-Chinese translation of modal words shows the tendency to full correspondence in a greater extent, which is primarily conditioned by similar semantic relations (the reflection of an utterance logical evaluation), expressed by modal words in both studied languages. It should be noted that such factors as the diachronic feature of the Chinese language, stylistics, the acceptance and the non-acceptance of Russian language features influence the translation of modal words with the meaning of possibility from Russian to Chinese